The informal market: Don't overlook it - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Policies banning or ignoring informal milk markets are counterproductive. Kenya is a positive example of how introducing improved technologies and standards to milk producers and traders can boost food safety and generate economic returns.